A Rare Case of Parotid Gland Tuberculosis. (6th January 2021) - Singh, Deepshikha; Mishra, Sudhir
Abstract : Parotid gland tuberculosis is a very rare form of extrapulmonary tuberculosis, with less than 200 cases reported in literature. We describe a 10-year-old female who presented with a swelling in the left parotid region during the last month. CT scan neck revealed an abscess in the left parotid gland extending into the submandibular gland, muscles, and bone. Pus aspirated by FNAC showed acid fast bacilli in the ZN stain, and GeneXpert was positive for rifampicin-sensitive Mycobacterium tuberculosis . She was successfully treated with antituberculous therapy given for 6 months. Parotid gland tuberculosis, although rare, has a good prognosis with drug therapy. Surgery is rarely required.